An unexpected Earl - Harrington, Anna (Romance fiction writer) (Harrington, Anna (Romance fiction writer). Lords of the Armory., 2021)
Brandon Pearce, former brigadier and now the Earl West, is determined to help the girl he once loved save her property and the charity she's been struggling to build. But he'll have to deceive her first... Twelve years ago, Brandon Pearce had to give up the girl he loved, Amelia Howard. Now Amelia is a grown woman with a past she desperately needs to keep hidden in order to save her brother Frederick's reputation. In an effort to avoid blackmail, Frederick needs to place a list of gentlemen into government positions, and for that, he'll need an ally in Parliament<U+2015>Pearce. Pearce has been investigating Scepter, a criminal group the Armory believes is behind the government appointments. Pearce must pretend that he sides with the blackmailer<U+2015>keeping someone else's secrets<U+2015>even though it means breaking Amelia's heart. But Pearce is willing to do anything he can for a second chance with her, even when he discovers she's been keeping secrets of her own.